Analysis and Design of Information Systems Self Check-In and Check-Out Web-Based Hotel - Auji Hamizan; Samsudin; Muhamad Alda (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Hotel is a designation for service providers in room service. In this industrial 4.0 era, hotels have developed a lot, especially in the field of technology in conducting room management. The use of this information system is very much needed for hotels in order to be able to collect guest data effectively and efficiently. However, by using the existing system, guest data in the process of staying can still be manipulated by hotel employees, especially irresponsible receptionists. In this study, analysis, design, and implementation of a self-check-in and check-out system were carried out which could reduce receptionist fraud in room management. This system also provides a Booking Engine so that guests can make room reservations independently and integrated directly with the Front Office System (FOS) for receptionist in room management. By implementing the function of the QR Code to carry out the check-in and check-out process independently, making receptionist access rights more limited, and room management becoming more transparent. This system is built using the PHP programming language, extreme programming development methods, and MySQL database. With the construction of a web-based hotel self check-in and check-out system, it can help simplify room reservations, room management, and reduce receptionist fraud in manipulating guest data.